Self-neglect among inmates of nursing homes and their non-inmate peers - AL-Quraishi, Habib Salman Mahmoud; Turki Nafil, Ali (Al-Adab Journal, 2020)
Self-neglect in the elderly is a condition resulting from the elderly’s disability due to a physical or psychological disability, or both, and the weakness of the ability to perform self-care that seriously threatens the elderly’s health, including hoarding, providing basic food, clothing, shelter, health care, and obtaining the goods and services needed to maintain On the physical and psychological health and public safety. The current research aims to measure self-neglect among the elderly and identify the differences in self-neglect among the elderly according to the gender variable (male - female), the living situation (retired - not retired), and housing (inside the homes for the elderly - outside the homes for the elderly). Some theories have been briefly reviewed in the theoretical framework, and the theory adopted is (Oremtheory). As for the sample, (380) elderly men and women aged (60) and over from Baghdad governorate (inside homes for the elderly and outside homes for the elderly). In order to measure self-neglect, the Self Neglect Scale was built and the following procedure: The tool was presented to a group of arbitrators, and the discriminatory force was measured and the relationship of the item to thesum total, validity and Reliability, and the psychometric properties of the tool were extracted. Note that the processing of the research data was carried out by statistical means that are compatible with thenature of the research and its objectives, through the Statistical Package for Social Sciences (SPSS). The results showed that the elderly do not suffer from self-neglect, and there are differences in the degrees of self-neglect among the elderly according to the gender variable (male - female), and there are no differences according to the living status variable (retired - not retired), and there are no differences in self-neglect according to the housing variable (within a role Elderly people - outside nursing homes). The research resulted in a number of recommendations and proposals.